2001
DOI: 10.1016/s0926-6410(01)00094-5
|View full text |Cite
|
Sign up to set email alerts
|

Human large-scale oscillatory brain activity during an operant shaping procedure

Abstract: The present study aimed at examining the oscillatory brain-electric correlates of human operant learning using high-density electroencephalography (EEG). Induced gamma-band activity (GBA) was studied using a fixed-interval reinforcement schedule with a variable limited hold period, which was decreased depending on response accuracy. Thus, participants' behavior was shaped during the course of the learning session. After each response, numbers indicating the money value of that response served as reinforcing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Analogous effects were observed in induced GBRs and phase locking among electrode sites. fMRI (R. and previous gamma-band findings during perceptual memory formation (Miltner et al, 1999;Keil et al, 2001b) suggest that these repetition-related increases might reflect encoding-related processes (i.e., the formation of new cell assemblies representing previously unfamiliar stimuli). This argument gains support from a previous repetition priming study using familiar and unfamiliar pictorial material, which showed a similar pattern of results (Gruber and Müller, 2005).…”
Section: Repetition By Stimulus Type Interactionmentioning
confidence: 72%
“…Analogous effects were observed in induced GBRs and phase locking among electrode sites. fMRI (R. and previous gamma-band findings during perceptual memory formation (Miltner et al, 1999;Keil et al, 2001b) suggest that these repetition-related increases might reflect encoding-related processes (i.e., the formation of new cell assemblies representing previously unfamiliar stimuli). This argument gains support from a previous repetition priming study using familiar and unfamiliar pictorial material, which showed a similar pattern of results (Gruber and Müller, 2005).…”
Section: Repetition By Stimulus Type Interactionmentioning
confidence: 72%
“…Our goal in this study was to show that by using a reward schedule based on behavioral shaping we could train subjects to increase the level of their neural responses in a specific brain region over time. Shaping schedules constantly adjust the threshold required to earn reward, based on subjects' previous performance, thus ensuring that subjects are in a state of constant learning (Keil et al, 2001). Our procedure succeeded not only in increasing activity over time but also in selectively increasing and decreasing activities in the specific ROIs, whereas activities in other regions recruited by this task remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Brock et al (2002) proposed that underconnectivity between separate functional brain regions in autism might be reflected in a lack of EEG synchrony in the gamma band (30 -80 Hz). In normal subjects, gamma activity is modulated by a variety of integrative processes, including feature binding (TallonBaudry et al, 1998), top-down feature selection (Hermann and Mecklinger, 2001), attention (Müller et al, 2000), face processing (Keil et al, 1999;Rodriguez et al, 1999), emotional arousal (Keil et al, 2001), and memory rehearsal (Tallon-Baudry et al, 1998. We are in the process of testing Brock's hypothesis using a delayed match-to-sample task, and preliminary data suggest abnormality of gamma activity over frontal cortex and visual processing areas during both stimulus encoding and memory rehearsal.…”
Section: Functional Anatomy In An Abnormally Wired Brainmentioning
confidence: 99%